Edukasi Literasi Keuangan bagi Pengurus Yayasan dan Keluarga Penyandang Disabilitas - Ekayana Sangkasari Paranita; Tatan Sukwika; Endang Wulandari (STKIP Andi Matappa, 2022)
This community service activity in financial literacy education was carried out at the Bogor City Foundation for Persons with Disabilities. The rise of financial technology-based applications has a worrying impact for people with disabilities because they do not understand reliable financial services. Their low financial literacy is vulnerable to being exploited by a number of parties who offer irrational financing and investments. This financial literacy education aims to increase the understanding of persons with disabilities on access to financial services. The method of activity begins with problem identification through meetings with foundations for persons with disabilities, followed by education through video screenings, posters, and financial literacy presentations. This activity was greeted with a very enthusiastic response from persons with disabilities and their families. After this activity took place, they understood more about bank and non-bank financial services, no longer believed in bombastic investment offers, realized the importance of saving, did not install unnecessary financial technology applications, and avoided online lending.